2004
DOI: 10.1002/art.20470
|View full text |Cite
|
Sign up to set email alerts
|

Reduced leukocyte–endothelial cell interactions in the inflamed microcirculation of macrophage migration inhibitory factor–deficient mice

Abstract: Objective. Macrophage migration inhibitory factor (MIF) is a proinflammatory cytokine with established roles in a range of inflammatory conditions. However, it is not known whether MIF influences inflammation via the direct promotion of leukocyteendothelial cell interactions. Therefore, the aim of these experiments was to investigate the ability of MIF to regulate leukocyte-endothelial cell interactions in the inflamed microvasculature.Methods. Intravital microscopy was used to examine postcapillary venules in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 46 publications
(67 reference statements)
4
65
0
2
Order By: Relevance
“…These experiments revealed that deficiency of MIF in HUVECs was associated with reductions in TNFinduced expression of adhesion molecules and chemokines, with concomitant reductions in TNF-induced leukocyte-endothelial cell interactions. These data are in agreement with our earlier observation of reduced TNF-induced rolling and adhesive interactions in postcapillary venules of MIF 2/2 mice following TNF treatment (14). In the current study, MIF deficiency also reduced basal endothelial cell expression of VCAM-1, ICAM-1, IL-6, IL-8, and MCP-1, suggesting that the presence of MIF contributes to constitutive expression of these molecules.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These experiments revealed that deficiency of MIF in HUVECs was associated with reductions in TNFinduced expression of adhesion molecules and chemokines, with concomitant reductions in TNF-induced leukocyte-endothelial cell interactions. These data are in agreement with our earlier observation of reduced TNF-induced rolling and adhesive interactions in postcapillary venules of MIF 2/2 mice following TNF treatment (14). In the current study, MIF deficiency also reduced basal endothelial cell expression of VCAM-1, ICAM-1, IL-6, IL-8, and MCP-1, suggesting that the presence of MIF contributes to constitutive expression of these molecules.…”
Section: Discussionsupporting
confidence: 94%
“…This indicated that exogenous MIF can facilitate the proinflammatory effects of TNF and LPS on leukocyte recruitment. Given the presence of extracellular MIF in normal plasma, this finding is likely to be relevant to the observation that MIF facilitates in vivo leukocyte-endothelial cell interactions induced by TNF or LPS (13,14). However, the finding that this effect was not associated with increased HUVEC expression of E-selectin, ICAM-1, VCAM-1, or various chemokines indicated the involvement of an alternative pathway for this effect, which we found to be induction of P selectin expression.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Abundant urine MCP-1 expression in MIF ϩ/ϩ MRL/lpr mice was associated with macrophage recruitment, both of which were significantly reduced in the absence of MIF. MIF has been shown to regulate leukocyte recruitment to the inflamed microvasculature in other tissues (44), and we have recently found that rMIF up-regulates endothelial cell MCP-1 expression and macrophage recruitment (62). It has been previously shown that the up-regulation of MCP-1 in the inflamed kidney interstitium in MRL/lpr mice is most striking in the tubular epithelial cells (26), in a similar distribution to that of MIF.…”
Section: Discussionmentioning
confidence: 99%
“…The synovial microcirculation was exposed for intravital microscopy as previously described. 30,31 Neutrophils were stained using PE-conjugated anti-Gr-1 mAb (2 g, intravenous injection), and 500 kDa FITC-dextran (17 g, intravenous injection; Molecular Probes) was used to delineate the microvasculature. Neutrophil rolling and adhesion were assessed in synovial postcapillary venules using a Leica SP5 multiphoton microscope (Leica-Microsystems) equipped with a 20ϫ, 1.0 NA objective and twin nondescanned detectors.…”
Section: Multiphoton Microscopy Of Synovial Microvessels In the Knee mentioning
confidence: 99%